Extralemniscal co-activation is not indispensable for behavioral detection of auditory stimuli - Jirsa, R; Poc, P; Radil, T (Behavioural brain research, 1993)
Thresholds for triggering summed auditory evoked responses (ERs) were measured in non-auditory (= extralemniscal--EL) nuclei receiving direct auditory projections from the lateral lemniscus. Primary EL ERs with onset latency of 3-6 ms reflecting activation of direct EL projections of lemniscal auditory nuclei were registered in caudal pontine reticular nucleus (CPRN), in deep layers of superior colliculus (SC) and in ventromedial hypothalamus (VMH). Secondary EL ERs (waves of EL ERs with onset latency above 10 ms) reflecting diffuse auditory EL co-activation of the brain, were registered besides the above mentioned nuclei also in the medial amygdala (MA). Threshold sound intensities for evoking primary EL ERs in CPRN, SC and VMH, for secondary EL ERs in all extralemniscal nuclei tested, and for conditioned avoidance behavior in a two-way shuttle box, were compared mutually. There were no significant mutual differences among thresholds for inducing secondary EL ERs in all EL nuclei tested. Thresholds for evoking secondary EL ERs were lower than those for evoking primary EL ERs in deep layers of the SC, equaled to thresholds for primary EL ERs in the VMH and were higher than thresholds for primary EL ERs in the CPRN. The results suggest that auditory EL projections into SC and/or VMH (but not into CPRN) might represent the primary triggering source for secondary EL ERs in various extralemniscal nuclei. Although conditioning lowered the threshold intensities for inducing secondary EL ERs, the threshold sound intensity for triggering conditioned behavior was lower than the threshold for secondary EL ERs.(ABSTRACT TRUNCATED AT 250 WORDS)
Keywords: Animals; Auditory Threshold; Evoked Potentials, Auditory; Brain Mapping; reakční čas; sluchové evokované potenciály; pons; Pitch Perception; vnímání hlasitosti; sluchová dráha; Vestibulocochlear Nerve; nervus vestibulocochlearis; mapování mozku; Loudness Perception; Auditory Perception; sluchová percepce; Pons; sluchový práh; Male; Reticular Formation; Mesencephalon; mezencefalon; krysa rodu Rattus; Auditory Pathways; vnímání výšky zvuku; Reaction Time; zvířata; mužské pohlaví; Rats; retikulární formace